Mathematics of MBBS Curriculum 2002 - Akhter, Nayeema (Journal of Chittagong Medical College Teachers’ Association, 2010)
DOI: 10.3329/jcmcta.v20i2.5617 Journal of Chittagong Medical College Teachers' Association 2009: 20(2):3-5